Theory of Dynamic Interactions: Laws of Motion - Barceló, Gabriel (Scientific research, 2013)
The aim of this paper is to present the laws of motion that can be derived from the Theory of Dynamic Interactions, and of its multiple and significant scientific applications. Based on a new interpretation on the behaviour of rigid bodies exposed to simultaneous non-coaxial rotations, we have developed a hypothesis regarding the dynamic behaviour of these bodies. From these hypotheses and following the observation of the behaviour of free bodies in space, we have developed axioms and a mathematical-physical model. Consequently, we have deduced a movement equation, coherent with the hypotheses and the observed behaviour. This dynamic model, in the case of rigid solid bodies or systems, allows putting forward a series of laws and corollaries in relation to its dynamic performance. These laws have subsequently been confirmed by experimental tests. The whole of this research constitutes a rational and conceptual structure which we have named Theory of Dynamic Interactions (TID). This logical deductive system allows predicting the behaviour of solid bodies subject to multiple accelerations by rotation. In the conclusions, we underline that coherence has been obtained between the principles and axioms, the developed physical-mathematical model, the obtained movement equation, the deduced laws and the realised experimental tests
Keywords: Dynamics Fields; Dynamical Systems Theory; Intrinsic Angular Momentum; Speeds Coupling; Theory of Dynamics Interactions